Enhancing early childhood emotional competence: A mixed-methods study of parental involvement and interactive media - Erin Erin; Zubaidah Zubaidah; Geby Velensia; Rita Markus Idulfilastri; Aloysius Bernanda Gunawan (Institut Agama Islam Negeri Langsa, 2026)
Emotion recognition is a foundational component of early childhood socio-emotional development, yet caregivers often lack structured educational media to systematically facilitate this learning within the home environment. This mixed-methods study aimed to evaluate the effectiveness of active parental involvement in habituating emotion recognition in children aged 4 to 6 years through interactive books. Employing a pre-experimental, one-group pre-test and post-test design, the study involved 10 child-parent dyads from the Jakarta and Tangerang regions during a one-week intervention. Quantitative data, analyzed using the Wilcoxon Signed-Rank test, revealed a statistically significant improvement in the children's emotion recognition abilities following the intervention (p=.011). Concurrently, qualitative data from in-depth parental interviews were analyzed using thematic analysis in NVivo. The qualitative findings demonstrated that parents employed highly fluid, situational parenting styles to scaffold their children's emotional learning. The interactive book not only served as an effective attentional deployment mechanism for the children but also fostered a reciprocal co-learning environment, thereby enhancing the children's emotional communication and the parents' behavioral regulation. Ultimately, the integration of multimodal interactive media with emotionally responsive parental scaffolding significantly advances early childhood emotional competence and fortifies intra-familial bonds.